2009
DOI: 10.1021/jm8012807
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Metabolite Changes in C6 Glioma Cells Cultured with Antimitotic Oleyl Glycoside by 1H MAS NMR

Abstract: The synthetic glycoside, oleyl N-acetyl-R-D-glucosaminide (1), was previously shown to exhibit antimitotic activity on rat (C6) and human (U-373) glioma lines. To obtain information about its mechanism of action, metabolite changes in C6 glioma cells were analyzed after treatment with 1 using high-resolution magic angle spinning 1 H NMR. Compound 1 caused either a decrease or an increase in the intensity of the signal assigned to coenzyme A (CoA) metabolites depending on the concentration used. The data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…The favorable effect of an oleyl chain on the antitumor activity was also observed in a family of alkylated iminosugars [6]. Further studies [7,8] designed to understand the mechanism behind the activity of 1 on lung carcinoma A549 and glioma C6 cells showed that, at concentrations above 30 µM, glycoside 1 drastically altered the cell lipid profile, with a significant increase in sphingolipid and glycosphingolipid levels, that eventually resulted in cell death [8]. Despite its promising activity against cancer cells in culture, glycoside 1 was inactive when tested in mice bearing an implanted C6 glioma.…”
Section: Introductionmentioning
confidence: 89%
“…The favorable effect of an oleyl chain on the antitumor activity was also observed in a family of alkylated iminosugars [6]. Further studies [7,8] designed to understand the mechanism behind the activity of 1 on lung carcinoma A549 and glioma C6 cells showed that, at concentrations above 30 µM, glycoside 1 drastically altered the cell lipid profile, with a significant increase in sphingolipid and glycosphingolipid levels, that eventually resulted in cell death [8]. Despite its promising activity against cancer cells in culture, glycoside 1 was inactive when tested in mice bearing an implanted C6 glioma.…”
Section: Introductionmentioning
confidence: 89%
“…While numerous HRMAS‐based studies have investigated well established chemotherapeutics, such as cisplatin, methotrexate (MTX), doxorubicin, tamoxifen, tyrosine kinase inhibitors, and bevacizumab—mostly focused on providing a more detailed understanding of the drugs' mechanisms of action and intracellular processes triggered by these drugs, such as apoptosis—others have explored the possibilities of new agents …”
Section: Evaluating Therapy Responsesmentioning
confidence: 99%
“…As mentioned above, HRMAS has also been used to study and develop new anti‐cancer agents and investigate their therapeutic efficacy against different cancer types …”
Section: Evaluating Therapy Responsesmentioning
confidence: 99%
“…The results obtained indicated that the activity was increased by a long hydrocarbon chain at position C-1 of the glucosamine backbone, the most inhibitory compound being the oleyl glycoside 2 (Chart 1). To obtain information about its mode of action, metabolite changes in C6 glioma cells were analyzed after treatment with glycoside 2, using high-resolution magic angle spinning (HR-MAS) 1 H NMR 371. The data obtained from the 1 H NMR spectra of the different experiments suggest that glycoside 2 inhibited cell division (IC 50 approx.…”
Section: Making Glioma Immunodetectablementioning
confidence: 99%
“…Determination of the precise structure of neurostatin required the purification of comparatively large amounts of the molecule. The fractionation of the amounts of brain tissue required was facilitated by preparation of ganglioside extracts 371. Neurostatin was purified from such extracts, using a combination of conventional and high performance ion-exchange and reverse phase chromatographies 357.…”
Section: Making Glioma Immunodetectablementioning
confidence: 99%